Application Analysis of Key Macroeconomic Indicators in Terms of Regional Disparity - Kondur, Oksana; Tomashevska, Antonina (Journal of Vasyl Stefanyk Precarpathian National University, 2021)
The purpose of the article is to study the causal links of the existence of disparities in the socio-economic development of the country's regions and identify key measures to overcome existing disparities in certain areas, taking into account systemic transformations in the modern economy. The main disparities in the regional development of Ukraine are considered and the criteria of regional disparities are defined. It is established that the largest disparities in regional development occur according to the indicators observed in the case of investment per capita. The regions-leaders and outsiders in terms of socio-economic development are selected according to the selected indicators.The division of regions of Ukraine is carried out by means of the cluster analysis. The regions are divided into groups with similar characteristics for the four analyzed macroeconomic variables. The distances between the clusters were expressed using the Euclidean distance, which is widely used in this type of analysis. To combine objects into groups, Ward's method was used to create clusters with a small number of objects.After the analysis, the following conclusions were made: across the country, the regions are characterized by large differences in the level of GRP per capita, capital investment per capita and unemployment, with smaller differences in income levels; an unfavourable phenomenon is the reduction of investment in the southern regions, which in fact leads to low economic growth and future trends; the condition for reducing regional disparities is overcoming barriers to the development of less developed regions, which may occur primarily through the consistent strengthening of their economy, improving the structure and more efficient use of investment resources aimed specifically at strengthening entrepreneurship and professional development.